Single cycle structure-based humanization of an anti-nerve growth factor therapeutic antibody. - Sonia Covaceuszach (Public Library of Science (PLoS), 2012)
Most forms of chronic pain are inadequately treated by present therapeutic options. Compelling evidence has accumulated, demonstrating that Nerve Growth Factor (NGF) is a key modulator of inflammatory and nociceptive responses, and is a promising target for the treatment of human pathologies linked to chronic and inflammatory pain. There is therefore a growing interest in the development of therapeutic molecules antagonising the NGF pathway and its nociceptor sensitization actions, among which function-blocking anti-NGF antibodies are particularly relevant candidates.In this respect, the rat anti-NGF αD11 monoclonal antibody (mAb) is a potent antagonist, able to effectively antagonize rodent and human NGF in a variety of in vitro and in vivo systems. Here we show that mAb αD11 displays a significant analgesic effect in two different models of persistent pain in mice, with a remarkable long-lasting activity. In order to advance αD11 mAb towards its clinical application in man, anti-NGF αD11 mAb was humanized by applying a novel single cycle strategy based on the a priori experimental determination of the crystal and molecular structure of the parental Fragment antigen-binding (Fab). The humanized antibody (hum-αD11) was tested in vitro and in vivo, showing that the binding mode and the NGF neutralizing biological activities of the parental antibody are fully preserved, with even a significant affinity improvement. The results firmly establish hum-αD11 as a lead candidate for clinical applications in a therapeutic area with a severe unmet medical need. More generally, the single-cycle structure-based humanization method represents a considerable improvement over the standard humanization methods, which are intrinsically empirical and require several refinement cycles.